Private Governance, State Regulation and Employment Standards: How Political Factors Shape their Nexus in Australian Horticulture - Underhill, Elsa; Rimmer, Malcolm (Relations industrielles / Industrial Relations, 2017)
The global weakness of collective bargaining and state regulation has spawned growing interest in employment protection though private governance. However, scepticism about the efficacy of unsupervised codes of conduct has triggered debate about external discipline through state regulation. This article seeks to contribute to debates about the processes that shape the nexus between private governance and state regulation.It is based on an empirical study of Australian harvest workers who formally benefit from state regulation of pay and occupational health and safety (OHS). However, industry changes have undercut standards. Product market pressures from supermarkets squeeze growers’ capacity to pay. Also, the labour market is increasingly supplied by vulnerable Asian temporary migrants (including undocumented workers), often supplied to growers by unscrupulous temporary work agencies. While pay and OHS practices vary, many harvest workers are exploited. Nor is private governance (which extends to horticulture through the codes of conduct of supermarkets and peak temporary work agency bodies) effective. All codes draw their standards from minimum legal employment conditions, and all possess loopholes allowing breaches to escape attention and rectification.In 2015, media and political attention fell on the working conditions of temporary migrants in horticulture. Government inquiries found evidence of exploitation, but were divided over solutions. Progressive politicians (influenced by unions) favoured stronger state enforcement powers and temporary work agency licensing. Conservative politicians (influenced by business lobbies) claimed these steps would fail, and favoured the status quo. Political reform therefore stalled.This study illustrates the importance of political processes in shaping the nexus between state regulation and private governance. In this case, a political stalemate leaves both regulation and governance deficient. Lacking protection from either source, harvest workers remain exposed to exploitative employment conditions.